Animal biodiversity: An update of classification and diversity in 2013. In: Zhang, Z.-Q. (Ed.) Animal Biodiversity: An Outline of Higher-level Classification and Survey of Taxonomic Richness (Addenda 2013) - Zhang, Zhi-Qiang (Zootaxa, 2013)
The kingdom Animalia is here estimated to have a total of 1,659,420 described species (including 133,692 fossil species) in 40 phyla. Among these, the most successful phylum Arthropoda alone represents 1,302,809 species, or about 78.5% of the total. The second largest phylum, Mollusca (118,061 species), is <10% of Arthropoda in diversity, but it is still much more diverse than other successful invertebrate phyla Platyhelminthes (29,488 species), Nematoda (25,043 species), Echinodermata (20,550 species), Annelida (17,426 species), Cnidaria (16,363 species), Bryozoa (11,474 species) and Porifera (10,876 species). The phylum Craniata, including the vertebrates, represents 85,432 species (including 19,974 fossil species): among these, 35,644 species of “fishes”, 7,171 species of amphibians, 15,507 species of reptiles, 11,087 species of birds, and 16,014 species of mammals.